Integrating the patient voice with clinician reports to identify a hepatocellular carcinoma-specific subset of treatment-related symptomatic adverse events - Rebecca M. Speck; William R. Lenderking; James W. Shaw (SpringerOpen, 2018)
Abstract Background Incorporating patient reporting of symptomatic adverse events (AEs) is important in evaluating safety and tolerability in cancer clinical trials. The Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) was developed to assess the frequency, severity, and/or interference of patient-reported symptomatic AEs. The objective of this study was to identify, based on oncologist and patient interviews, a relevant subset of symptomatic AEs from the PRO-CTCAE that can be used to optimize patient reporting of symptomatic AEs in hepatocellular carcinoma (HCC) clinical trials. Methods Qualitative and quantitative data on HCC diagnosis, treatment, symptoms, and side effects were collected from patients. Using a numerical rating scale, medical oncologists specializing in HCC rated the importance of (1) 34 symptomatic AEs (Grade ≥2) identified in past sponsor HCC clinical trials, (2) each PRO-CTCAE symptomatic AE item to the patient, and (3) each PRO-CTCAE symptomatic AE item with respect to patient safety or tolerability. Patients completed the PRO-CTCAE items and were debriefed on the importance of each PRO-CTCAE symptomatic AE to them. Results Five medical oncologists from the United States, Spain, Taiwan, Korea, and Hong Kong with 14 to 30 years of experience, and 17 patients with HCC and Child-Pugh class A or B cirrhosis status completed interviews. Medical oncologists rated the following symptomatic AEs from prior trials as being highly important to patients (mean rating of ≥7 on a scale from 0 to 10): hand-foot syndrome, diarrhea, fatigue, decreased appetite, rash, vomiting, and weight loss. PRO-CTCAE symptomatic AEs rated by medical oncologists as being highly important to patients included diarrhea, vomiting, shivering or shaking chills, hand-foot syndrome, rash, fatigue, difficulty swallowing, decreased appetite, and loss of control of bowel movements. Patients rated the following PRO-CTCAE symptomatic AEs as being highly important: loss of appetite/lack of interest in food, pain/tenderness at injection/insertion site, fatigue/lack of energy/tiredness, nausea, and hair loss. Conclusions This study identified a preliminary list of clinically relevant symptomatic AEs from interviews with both medical oncologists and patients that can be used to support assessments of treatment safety and tolerability in HCC clinical trials.